Pendidikan Anak Usia Dini Children Well-Being Dan Implikasinya Terhadap Kualitas Pendidikan Anak Usia Dini: Tinjauan Perkembangan Psikologis - Mohamad Keisa Mubarok; Risbon Sianturi; Taopik Rahman; Agni Azalia Rusmawa; Ayu Tri Indah; Neishya Maulani Budiman (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the concept of children’s well-being and its relationship with the quality of early childhood education. This research uses a qualitative approach through a literature review method, with data sources obtained from Google Scholar, PubMed Central, and ScienceDirect. Articles were selected based on relevance, publication within the last ten years, and full-text availability. Data were analyzed using content analysis to identify key themes. The findings show that children’s well-being is multidimensional, including emotional, social, cognitive, and environmental aspects. It influences children’s readiness, engagement in learning, and overall development. Children with good well-being tend to be emotionally stable, more active, and better able to adapt. In contrast, unfavorable conditions may hinder the learning process. The study also reveals a reciprocal relationship between well-being and learning experiences. Therefore, improving early childhood education should place children’s well-being as a fundamental basis through safe environments, positive interactions, and child-centered learning